Мактабгача таълим муассасаси фаолиятини ташкил этишда тарихий тажриба ва замонавий маданият уйғунлиги - Кенжаева, Д.Т; Йўлдошева, Ф (SCIENCE and SOCIETY, 2019)
This article discusses the historical experience and the combination of modern culture in the organization of preschool education,as well as the problems of solving these important factors.
Keywords: preschool education; historical experience; contemporary culture; harmony; innovative approach